On some theoretical and methodological issues in researching the Roma population in sociology and ethnology/socio-cultural anthropology. The example of an ongoing research project in Serbia - Miloš Milenković (Etnoantropološki Problemi, 2016)
The paper considers theoretical and methodological problems noted during the research project “Social and cultural potentials of the Roma ethnic community in Serbia” undertaken during 2013 and 2014. These problems point to an extant yet latent tension between the anthropological and the sociological approaches to the researched reality, with special emphasis on the antirealist tradition of the former and the empiricist “realist” tradition of the latter in the Serbian academic tradition of these disciplines. The paper considers how standard issues connected to methodological aspects of this primarily sociological research project (choice of topic, creation of sample, the making of field instruments, selection of informants, communication in the field, use of field assistants, data analysis and the making of the manuscript) diffract through the prism of theoretically disputable concepts of identity, ethnicity, assimilation and essentialization, which are subject to continuing questioning in anthropological theoretical and empirical research. The experience of conducting research together displays a set of methodological defaults on the anthropological and a set of theoretical defaults on the sociological side, followed by research renunciations and interpretative tensions and frustrations that arise from them, so it can be used as a guide to understanding disciplinary differences and similarities, especially when planning cooperation on a global level as well as in the local research context. Aside from this, the indivisibility of theoretical and methodological structures and the huge influence of theory on method, as demonstrated by the research itself, is considered, with implications for understanding theoretical and methodological issues which are bigger than the two disciplines in question. It is concluded that, for pragmatic reasons, multidisciplinary research of this type must be designed to suppress the theoretical ambitions of anthropology as well as the methodological ambitions of sociology.